Effect of oral supplementation of palm oil tocotrienol-rich fraction on gametes and reproductive organ of female rats / Fakhrur Razi Jamal - Jamal, Fakhrur Razi (2015)
The world statistic on female infertility were accounted more than 12.4% which aged around 22 to 44 years old The current treatment on infertility problem shows some adverse effect that affecting a women health However, the palm oil tocotrienol-rich fraction (TRF) that one of the vitamin E isomer were known to have potential health benefit towards human such as anti-cancer and anti-proliferative. This study were performed to investigate the improvement of female reproductive system through oral supplementation of palm oil TRF. TRF were diluted with corn oil as a vehicle. Thirty (30) female of Wistar albino rats were randomly divided into five group (n=6) which are, negative control group administrated orally with distilled water, positive control group administrated orally with corn oil and treatment groups were administrated orally with different TRF concentration which are 30 mg/kg, 60 mg/kg and 90 mg/kg. On day five and seven, the rats were superovulated by injection of PMSG and hCG hormone. The euthanized process were done after 24 hours of hCG injection and the blood were collected for blood analysis. The oviduct were collected for oocyte count and grading as well as ovary for histology study The ovary group shows no significant different between negative control groups and three different concentration of TRF treated group, Meanwhile, the group 60 mg/kg shows the increased of oocyte count and quality but were not significant. 60 mg/kg and 90 mg/kg of TRF treated group shows significant higher of ovarian surface epithelial which suggested proliferation process. Three different TRF concentration treated group shows no hepatotoxicity effect. While, 90 mg/kg of TRF treated group shows nephrotoxicity effect with significant increase of urea. This present study suggested the 60 mg/kg of TRF might have potential effect on improvement of female reproductive system by increase the nocytc count and quality. However, the proliferation of OSE still remain unclear either due to physiological changes or pathological changes,